Perceptions of family‐centred care among caregivers of children with cerebral palsy in South India: An exploratory study. (28th November 2021) - Poojari, Deepalaxmi Paresh; Umakanth, Shashikiran; Maiya, G. Arun; Rao, Bhamini Krishna; Brien, Marie; Narayan, Amitesh
Abstract: Background: Parental views and expectations about family‐centred care (FCC) need to be understood for its successful implementation. Knowledge of caregiver's perceptions and needs, within their social and cultural context, forms the basis for effective health care partnerships with families. The purpose of this study was to explore perceptions about FCC among caregivers of children with cerebral palsy (CP) in South India. Method: Fourteen caregivers of children with CP (aged 4–12 years) living in rural areas of the coastal region of Karnataka, India, participated in this qualitative study. Face‐to‐face semi‐structured interviews were recorded and transcribed for analysis using the framework and hybrid approaches. Thematic mapping of the categories and themes was done to explore relationships about perceptions of FCC. Results: Caregiver's life emerged inductively as a new theme highlighting caregiver's own physical and mental health, family roles and well‐being, integrating the onus of care with household responsibilities, limited participation in personal activities and social isolation. The qualitative findings revealed the ubiquity of respectful and trusting relationships with health professionals while expressing paucity of coordinated comprehensive care, sporadic partnerships and opportunities for shared decision‐making; desire for receiving specific information related to child's progress and prognosis; and general information on community resources and the need of empowerment and support groups. Conclusion: Our study has practical implications for the implementation of FCC within the South Indian context, by recognizing unique caregiver needs and expectations in sync with cultural perspectives towards childhood disability such as societal stigma, values and traditional beliefs; attitudes towards medical professionals; and life stressors and gender responsibilities.